2015
DOI: 10.1111/ijfs.12800
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of films from xylose‐glycosylated peanut protein isolate powder

Abstract: Summary This work aimed at producing and characterising xylose‐glycosylated peanut protein isolate (PPI‐X) films by dissolving PPI‐X powder in water at ambient temperature and further plasticising with glycerol. The effect of powder dissolution temperature (20–100 °C) and glycerol concentration (15.0–45.0%, w/w) on mechanical properties and integrity of these films was quantified. The results showed that the powder dissolution temperature had no significant effect on the mechanical and water resistance propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Numerous previous studies have indicated a signicant improvement of the functional properties of products coming from Maillard reaction between polysaccharides and proteins. 4,17 In order to determine the effect of glycosylation on structural properties of xylose-modied PPI powder, the degree of glycosylation (DG) with different xylose ratio was determined. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous previous studies have indicated a signicant improvement of the functional properties of products coming from Maillard reaction between polysaccharides and proteins. 4,17 In order to determine the effect of glycosylation on structural properties of xylose-modied PPI powder, the degree of glycosylation (DG) with different xylose ratio was determined. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] In literature, several recent papers deal with the improvement of the mechanical and barrier properties of protein-based lms by glycosylation reactions. 4,9,10 Glycosylation with gum arabic 11 or glucomannan 9 increases the tensile strength, decreases the water vapor permeability of protein lms, but decreases the elongation ability. Generally, plasticizers having a smaller molecular weight show an easier incorporation into the protein matrix than plasticizers with a larger molecular weight.…”
Section: -4mentioning
confidence: 99%
See 3 more Smart Citations